Trends in anecdotal fox sightings in Tasmania accounted for by psychological factors. Issue 6 (26th August 2017) - Marks, Clive A.; Clark, Malcolm; Obendorf, David; Hall, Graham P.; Soares, Inês; Pereira, Filipe
Abstract: There has been little evaluation of anecdotal sightings as a means to confirm new incursions of invasive species. This paper explores the potential for equivocal information communicated by the media to account for patterns of anecdotal reports. In 2001, it was widely reported that red foxes (Vulpes vulpes) had been deliberately released in the island state of Tasmania (Australia), although this claim was later revealed to be baseless. Regardless, by 2013 a total of 3153 anecdotal fox sightings had been reported by members of the public, which implied their distribution was wide. For each month in 2001–2003, we defined a monthly media index (MMI) of fox‐related media coverage, an index of their relative seasonal abundance (abundance), and a factor denoting claims of fox evidence (claimed evidence) regardless of its evidentiary quality. We fitted a generalized linear model with Poisson error for monthly totals of anecdotal sightings with factors of year and claimed evidence and covariates of MMI, abundance, and hours of darkness. The collective effect of psychological factors (MMI, claimed evidence, and year) relative to biophysical factors (photoperiod and abundance) was highly significant (χ 2 = 122.1, df = 6, p < 0.0001), whereas anticipated changes in abundance had no significant influence on reported sightings ( p = 0.15). An annual index of fox media from 2001 to 2010 was strongly associated with the yearly tally of anecdotal sightings ( p = 0.018). The odds ratio of sightings ranked as reliable by the fox eradication program in any year decreased exponentially at a rate of 0.00643 as the total number of sightings increased ( p < 0.0001) and was indicative of an observer‐expectancy bias. Our results suggest anecdotal sightings are highly susceptible to cognitive biases and when used to qualify and quantify species presence can contribute to flawed risk assessments.